1977
DOI: 10.1085/jgp.70.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Nystatin as a probe for investigating the electrical properties of a tight epithelium.

Abstract: 90024.n B S T R A C T We show how the antibiotic nystatin may be used in conjunction with microelectrodes to resolve transepithelial conductance G t into its components: Ga, apical membrane conductance; Gbl, basolateral membrane conductance; and Gj, junctional conductance. Mucosal addition of nystatin to rabbit urinary bladder in Na+-containing solutions caused Gt to increase severalfold to ca. 460/~mho/p.F, and caused the transepithelial voltage V t to approach +50 mV regardless of its initial value. From mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
2

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(117 citation statements)
references
References 18 publications
8
107
2
Order By: Relevance
“…In the first phase the TEV hyperpolarized, the conductance and I sc increased, and the C T increased to ϳ100% over starting values ( Figure 4A). Because ion transport across the apical membrane of the umbrella cell is the primary contributor to transepithelial conductance (Lewis et al, 1977), and because C T increased, the changes we observed in phase 1 likely reflected increased ion transport and membrane traffic at the apical plasma membrane domain of the umbrella cells. During the second phase of outward bowing the C T , I sc , and TEV rapidly reversed course ( Figure 4A).…”
Section: Umbrella Cell Electrophysiological Properties Are Sensitive mentioning
confidence: 83%
“…In the first phase the TEV hyperpolarized, the conductance and I sc increased, and the C T increased to ϳ100% over starting values ( Figure 4A). Because ion transport across the apical membrane of the umbrella cell is the primary contributor to transepithelial conductance (Lewis et al, 1977), and because C T increased, the changes we observed in phase 1 likely reflected increased ion transport and membrane traffic at the apical plasma membrane domain of the umbrella cells. During the second phase of outward bowing the C T , I sc , and TEV rapidly reversed course ( Figure 4A).…”
Section: Umbrella Cell Electrophysiological Properties Are Sensitive mentioning
confidence: 83%
“…Indeed, recent work has shown that ENaC can be rapidly controlled via changes in internal [Na ϩ ] and [Cl Ϫ ] (8,22), and it is very unlikely that such ionic control of G Na ϩ (8,22) would be detected in studies of basolaterally permeabilized cells. In this experimental situation, transient changes in internal ionic composition may occur as apical conductances are activated, but the relatively large volume of the external solution implies that such changes would be rapidly compensated for by ions entering/leaving the cytoplasm via the permeabilized membrane (21). The present estimates of G Na ϩ were thus made under relatively constant ionic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds form pores in cholesterol-containing membranes that are permeable to Na ϩ , K ϩ , and Cl Ϫ but not to divalent cations or highermolecular-weight substances and thus allow experimental control over the cytoplasmic [Na ϩ ], [K ϩ ], and [Cl Ϫ ], whereas intracellular Ca 2ϩ is regulated by the normal, physiological mechanisms. Because the pores formed by amphotericin B have a higher Cl Ϫ conductance than do those formed by nystatin (13,21), the former compound was used to make measurements of GClϪ.…”
Section: Isolation and Culture Of Rat Fetal Distal Lung Epithelial Cementioning
confidence: 99%
See 1 more Smart Citation
“…The tissue was dissected, mounted according to the procedures of , and placed between modified Ussing chambers (15 ml./chamber) which were designed to eliminate edge damage and to reduce hydrostatic gradients during micro-electrode impalements (Lewis, Eaton, Clausen & Diamond, 1977). The exposed area of tissue was 1 cm2.…”
Section: Methodsmentioning
confidence: 99%